2020
DOI: 10.13075/ijomeh.1896.01422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the police operational tactical procedures for reducing officer injuries resulting from physical interventions in problematic arrests. The case of the Municipal Police of Cádiz (Spain)

Abstract: Objectives: This paper describes some operational tactical procedures (OTP) and discusses the results of a 14-year-long study, spanning the period 2003-2016, conducted by the Municipal Police of Cádiz, Spain, which comprised 3 time periods: 2003-2006, when the officers were trained in traditional policing procedures; 2007-2013, when the officers were taught an innovative set of OTP in the form of a basic set of self-defense and arrest mechanisms, different from the traditional policing procedures that rely on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Only five original studies were found, which was not expected. Our main findings are that all studies analyzed how MA/F/CS can help police officers in carrying out their duties even in stressful situations (RENDEN et al, 2015;RENDEN et al, 2015a;TORRES, 2018;STALLER et al, 2017) and how its practice can prevent injuries and reduce medical certificates (JIMÉNEZ et al, 2020). Figure 1 illustrates the main findings of this study.…”
Section: Sourcesmentioning
confidence: 58%
See 1 more Smart Citation
“…Only five original studies were found, which was not expected. Our main findings are that all studies analyzed how MA/F/CS can help police officers in carrying out their duties even in stressful situations (RENDEN et al, 2015;RENDEN et al, 2015a;TORRES, 2018;STALLER et al, 2017) and how its practice can prevent injuries and reduce medical certificates (JIMÉNEZ et al, 2020). Figure 1 illustrates the main findings of this study.…”
Section: Sourcesmentioning
confidence: 58%
“…For Irving, Orr and Pope (2019), police officers must be conditioned to carry out their tasks. Another important aspect of the practice of MA/F/CS in police officers is the reduction of injuries during work and medical leaves (JIMÉNEZ et al, 2020). The decrease in injuries by these police officers may be because the techniques learned in MA/F/CS have the effect of preventing injuries caused by everyday situations (for example, falling) (BOGUSZEWSKI et al ., 2015).…”
Section: Sourcesmentioning
confidence: 99%
“…It should not be forgotten that over the last few years new tools or technologies have been incorporated to police intervention equipment (conducted energy devices -DEC-or pepper sprays). Although their use has caused a great deal of public outrage and widespread media coverage, it has been overlooked that the problems arising from their use were often attributable to specific circumstances such as positional asphyxia, pre-existing diseases or substance abuse (MacDonald, 2009) [23].…”
Section: Introductionmentioning
confidence: 99%
“…Police officers on patrol face different challenging contexts from a mental, social and physical point of view that can affect their life and health [7][8][9]. These concerns encouraged Vera-Jiménez [10] to conduct a local-scale study in Cádiz, a town in southern Spain with a population of slightly over 100,000 inhabitants. The study consisted on providing a group of municipal police officers with specific training based on OTP procedures [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It could be concluded that thanks to the employment of these procedures, the sick leaves of the officers were substantially reduced during the training period and for a certain period right after the training had been completed with respect to other periods when no OTP education had been provided. Unlike the currently endorsed classical police training methods, which are based on military instruction, martial arts and other fight and combat sports (MA/F/CS), OTP procedures have been developed in contrast to classical police training [13] for two reasons: a) The harm caused to the concerned citizens when subjected to Physical Intervention Techniques (PITs) [10,14] and b) The high risk of injury for the police officers when performing such PITs [10,12,15]. Thus, in Vera-Jiménez' study [10] an anatomical map was already designed to indicate the areas of the human body of the citizens for which PITs were either recommended or forbidden.…”
Section: Introductionmentioning
confidence: 99%